AN ANALYSIS OF SLANG EXPRESSION TRANSLATION IN MOVIE - Dio Resta Permana (Global Expert: Jurnal Bahasa dan Sastra, 2022)
Slang is a language that is often used in society. The use of this variety of languages shows that there is a fairly good closeness between the speakers in communication. In this research, it is expected to find out how the description of the use of language, especially the existence of Slang. This study applied the Content Analysis technique. The qualitative descriptive approach is used as the research methodology in this study. This is due to the fact that the researcher analyzed the data descriptively and the conclusion was offered in the form of an explanation of words. From the study, it found that the translator tent to use equivalent words that have similarities in meaning between ST and TT, so it guides the audience easily understood the meaning of Slang words. The translator also tends to use ‘softened word’ in TT in order to avoid the vulgarity and rudeness of ST. In contrast, it also found that the translator did some mistakes in translating slang from ST. This mistake can be avoided by the translator by knowing the cultural background of the slang word first, then looking for relevancy between utterance and context, and last the translator need to pick up the equivalent word in TT that has a similar meaning to the slang word in ST.